The Influence of Principal Leadership Style on Teacher Performance - Muhammad Nur Rasyid (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this article is to determine whether the principal's leadership style influences teacher performance. This qualitative research employed a literature review method, which examined several national articles. The results indicate that the principal's leadership style has both positive and negative effects on teacher performance in schools. The various leadership styles include transformational leadership, charismatic leadership, transactional leadership, autocratic leadership, bureaucratic leadership, and democratic leadership.